Interval training for performance: a scientific and empirical practice. Special recommendations for middle- and long-distance running. Part II: anaerobic interval training - Billat, L. V. (Sports Medicine, 2001)
Studies of anaerobic interval training can be divided into 2 categories. The first category (the older studies) examined interval training at a fixed work-rate. They measured the time limit or the number of repetitions the individual was able to sustain for different pause durations. The intensities used in these studies were not maximal but were at about 130 to 160% of maximal oxygen uptake (VO2max). Moreover, they used work periods of 10 to 15 seconds interrupted by short rest intervals (15 to 40 seconds). The second category (the more recent studies) asked the participants to repeat maximal bouts with different pause durations (30 seconds to 4 to 5 minutes). These studies examined the changes in maximal dynamic power during successive exercise periods and characterised the associated metabolic changes in muscle. Using short-interval training, it seems to be very difficult to elicit exclusively anaerobic metabolism. However, these studies have clearly demonstrated that the contribution of glycogenolysis to the total energy demand was considerably less than that if work of a similar intensity was performed continuously. However, the latter studies used exercise intensities that cannot be described as maximal. This is the main characteristic of the second category of interval training performed above the minimal velocity associated with VO2max determined in an incremental test (vVO2max). Many studies on the long term physiological effect of supramaximal intermittent exercise have demonstrated an improvement in VO2max or running economy.